2009
DOI: 10.1002/hlca.200900022
|View full text |Cite
|
Sign up to set email alerts
|

Tri‐ and Bicyclic Taxoids from the Taiwanese Yew Taxus sumatrana

Abstract: Five new taxoids, including a new 2(3 ! 20)-abeo-taxane with a 6/10/6-membered ring system and four 3,8-seco-taxanes having a 6/12-membered ring system, were isolated from an acetone extract of the leaves and twigs of the Taiwanese yew (Taxus sumatrana, Taxaceae). The structures were established as 2a,7b,10a-triacetoxy-5a-hydroxy-2(3 ! 20)-abeo-taxa-4(20),11-dien-9,13-dione (1), (3E,8E)-2a,9,10b, 13a,20-pentaacetoxy-7b-hydroxy-3,8-secotaxa-3,8,11-trien-5-one (2), (3E,8E)-2a,9,10b,13a,20-pentaacetoxy-5a,7b-dihy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…14,15) Compound 2 was therefore unambiguously characterized as 2,7,10-triacetoxy-5-hydroxy-2(3!20)abeotaxa-4(20),11-diene-9,13-dione. It should be noted that the 10-epimer of 2 has recently been isolated from the bark of T. sumatrana, 17) in which the 1 H-NMR chemical shift of H-C(10) was significantly different ( 5.69 ppm, 6.43 ppm for 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15) Compound 2 was therefore unambiguously characterized as 2,7,10-triacetoxy-5-hydroxy-2(3!20)abeotaxa-4(20),11-diene-9,13-dione. It should be noted that the 10-epimer of 2 has recently been isolated from the bark of T. sumatrana, 17) in which the 1 H-NMR chemical shift of H-C(10) was significantly different ( 5.69 ppm, 6.43 ppm for 1).…”
Section: Resultsmentioning
confidence: 99%
“…The locations of the acetyl groups were deduced from the HMBC correlations of carbonyl carbons with corresponding protons. The signal at C 78.2, which showed long-range correlations with H-C(9), H-C(10), Me (16) and Me (17) in the HMBC experiment, was assigned to C (11), and a hydroxy group attached to C(11) was suggested by its chemical shift value and molecular formula. The olefinic carbon at C 132.5, which showed HMBC correlations with H-C (10) and Me(18), was assigned to C(12).…”
mentioning
confidence: 94%
“…In 2009, four novel taxane diterpenoids (2.1.29-2.1.32) (Figure 8.6) possessing an unusual 6/12-membered ring system were discovered from an acetone extract of the leaves and twigs of Taxus sumatrana [30]. The preliminary in vitro biological evaluations revealed that taxoids 2.1.…”
Section: New Taxanesmentioning
confidence: 99%
“…The tasumatrols A-Z were reported isolated from leaves and twigs [10][11][12][13][14][15]. The leaves and twigs also isolated Taiwantaxins A-D isolated [16] and other chemical compounds [17,18]. Some of the isolated compounds reported have cytotoxic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the isolated compounds reported have cytotoxic activities. Among them are wallifoliol (KB and Hepa 59 T/VGH), taxuspine F, and 3, 6, 7, 10-deacetylbaccatin III (Hepa cells), tasumatrol F (A-498, NCI-H226, A549, and PC-3 tumor cells), Tasumatrols I and K (Hepa59T/VGH, NCI, HELA, DLD-1, and Med cell lines), tasumatrol P (HELA and Daoy tumor cells), tasumatrol Z (Hep2 cell line), and Taiwantaxin B (PC-3 tumor cells) [9][10][11][12][13][14][15][16][17]. The results of clinical studies also indicated that paclitaxelcontaining regimens on breast cancer patients provided additional benefits [19].…”
Section: Introductionmentioning
confidence: 99%